Informal Education The Rural Precedent and the Urban Challenge / Paul A. Miller. - Miller, Paul A., 1917-2015 (Distributed by ERIC Clearinghouse, 1968)
For the university to be of service, it must be attuned to urban life. Some educators have suggested that a special chain of urban grant universities could reproduce in the cities the success of the landgrant colleges with rural society. The question is: Is the rural precedent really pertinent to contemporary urban needs? Analogies from urban problems to rural problems will not easily give us the methodology necessary for improving the quality of urban life. The rural precedent, however, teaches us something of the need we have of a design for urban development. The community, itself, has become the classroom; and thus a new conception of community education may be evolving. (se)